PERSEPSI ORANG TUA DI KAMPUNG ADAT CIREUNDEU TENTANG PENDIDIKAN ANAK USIA DINI - Fitri Andriani, - (2021)
This study aims to determine how parents perceive early childhood education, determine the factors that influence parents 'views, and whether culture determines parents' perceptions of early childhood education. Participants in this study were parents who have children aged 2-6 years and elders. Participants totaled 4 people, consisting of 2 fathers, 1 mother, and 1 elder. The approach used is a qualitative approach with a case study method. The data collection technique used semi-structured interviews. Data validation was performed using source triangulation. The data analysis technique used is grounded theory analysis technique. Based on the results of data analysis, the findings of this study can be stated as follows: (1) early childhood education (PAUD) as a place of learning for children to develop aspects of development; (2) applying the motto "SILAS" in educational practice; (3) education following the development of the era of "Ngindung Kawaktu Mibapa Ka Jaman"; (4) collaborating formal education with local wisdom. The conclusion of this research is that the people in the Cirendeu traditional village have an educational philosophy, namely "protecting kawaktu mibapa ka era" and education departs from the terms Silih Asah, Silih Asih, Silih Asuh (Silas). The concept of education in the traditional village of Cirendeu is very interesting, namely that there is indigenous education that specifically educates children to adulthood from generation to generation with cultural values as its foundation. The results of this discovery are expected to be an effort to preserve and develop the existing culture in traditional villages, as well as add insight in knowing about the philosophical education that exists in the Cirendeu traditional village.